Meta-analysis: COVID-19 Disease Severity Correlates With Smoking Status. Issue 4 (10th July 2020) - Lansiaux, Édouard; Pébaÿ, Philippe P.; Picard, Jean-Laurent; Forget, Joachim
Abstract : The novel Coronavirus Disease 2019 (COVID-19) disease is a contagious acute respiratory infectious disease whose causative agent has been demonstrated to be a new virus of the coronavirus family, severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Multiple studies have already reported that risk factors for severe disease include older age and the presence of at least one of several underlying health conditions. However, a recent physiopathologic report and the French COVID-19 scientific council have postulated a protective effect of tobacco smoking. Thanks to a meta-analysis, we have been able to demonstrate the statistical significance in this regard of 12 series from China, France, and the United States, reporting 3 different smoking statuses (current smoker, former smoker with a smoking history) and disease severity [with odds ratio of 1.78 (1.08-3.10), 4.60 (3.13-7.17), 2.74 (0.63-5.89), respectively]. Subsequently, and using a Bayesian approach, we have established that past and present smoking is associated with more severe COVID-19 outcomes. Finally, we refute claims linking general population smoking status [N=O(10 8 ) or O(10 9 )] to much smaller disease course series [N=O(10 4 )]. The latter point, in particular, is presented to stimulate academic discussion, and must be further investigated by well-designed studies.